PERCEPTIONS ABOUT REFRACTIVE ERRORS AMONG ORANG ASLI ADULTS IN KUANTAN, PAHANG: A GROUNDED THEORY ANALYSIS - Hashim, Ain Syafa Nabila; Musa, Azuwan (International Journal of Allied Health Sciences, 2021)
Aims: This research aim is to investigate the understanding and perceptions of Orang Asli adults in Kuantan, Pahang about refractive errors. Methodology: Six villages of Orang Asli in Kuantan, Pahang were selected, and two persons were interviewed from each village. The concept and key word from the interview were being identified and combined to be grouped up into one specific characteristic and categories. Results: Theoretical conceptualization that describes perceptions and knowledge of Orang Asli adults regarding refractive errors were obtained which are definitions, types, causes, effects on daily activities and treatments. Conclusion: Orang Asli has acceptable knowledge and understanding regarding the refractive errors as many of the answers can be answered correctly. Keywords: Orang Asli, refractive errors, visual impairment